2019
DOI: 10.31083/j.jin.2019.04.1192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of remote limb ischemic conditioning on poststroke cognitive impairment

Abstract: J o u r n a l o f I n t e g r a t i v e N e u r o s c i e n c e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 78 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…The grand-average peak amplitudes and latencies of the three components were calculated separately at F3, Fz, F4, C3, Cz, C4, P3, Pz, and P4. These areas are the ones usually activated by the stimuli (Choo et al, 2005;Verweij et al, 2014;Jin et al, 2015;Lei et al, 2015;Feng et al, 2019;Ueda and Nakao, 2019;Wang et al, 2019;Khedr et al, 2020).…”
Section: Erp Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…The grand-average peak amplitudes and latencies of the three components were calculated separately at F3, Fz, F4, C3, Cz, C4, P3, Pz, and P4. These areas are the ones usually activated by the stimuli (Choo et al, 2005;Verweij et al, 2014;Jin et al, 2015;Lei et al, 2015;Feng et al, 2019;Ueda and Nakao, 2019;Wang et al, 2019;Khedr et al, 2020).…”
Section: Erp Preprocessingmentioning
confidence: 99%
“…P300 is the largest positive-going peak amplitude of the waveform within a time window of 300-400 ms and is considered to represent the allocation of attentional resources to rare salient stimuli (Cote et al, 2001;Marhöfer et al, 2015). P300 amplitude and latency are thought to reflect cognitive processing, such as stimulus identification and evaluation (Feng et al, 2019;Wang et al, 2019;Gao et al, 2020;Khedr et al, 2020). Studies have also suggested that higher-order cognitive stimulielicited P300 components are generated from the anterior cortex, and these components reflect the response inhibition process (de Bruijn et al, 2020;Paul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In four studies, the effect of RIC was investigated in patients who were not eligible for revascularization therapies. 32 , 33 , 34 , 35 In three studies, RIC was applied as an add‐on for treatments of thrombolysis by intravenous alteplase 36 , 37 or thrombectomy. 38 One study included patients receiving additional medical treatment and patients not eligible for thrombolysis or thrombectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of patients who did not undergo additional revascularization initiated RIC within 24 h from stroke onset 32 or 24–72 h (with subsequent daily sessions up to 14 days 33 ). Two studies did not indicate when RIC was initiated, 34 , 35 revealing only that one inclusion criterion was a symptom onset between 4.5 h and 14 days prior to the initiation of RIC. 35 The study that included patients with and without additional medical revascularization included patients within 6 h from disease onset and had three groups.…”
Section: Resultsmentioning
confidence: 99%
“…There was also a dose-dependent improvement in survival at 84 days by Kaplan-Meier analysis in separate experiments 26 . Many clinical studies also support that CRIC brings bene ts in various conditions, including healing of diabetic foot ulcer 27 , stroke recurrence in patients with symptomatic atherosclerotic intracranial arterial stenosis 28 , and cognitive domains in patients with non-cardiac ischemic stroke 29 . observed that AF recurrence in the 3 months after the PAF ablation was signi cantly lower in the RIC group than in the control group.…”
Section: Discussionmentioning
confidence: 97%